Le Fleur Enterprise / Nur Aisyah Ahmad ... [et al.] - Ahmad, Nur Aisyah; Rosli, Izzati Nadzirah; Mad Rodi, Alia Shazwani; Ahmad Zafir, Noor Alia Humairah (2021)
Le Fleur Enterprise by HANA are selling 3 types of products which is bouquet flower, indoor flowers and others side product which we choose the best quality from the supplier and maintain its freshness. We choose to sell these beautiful creature because in Malaysia there a numerous Celebration and Festival that flowers suitable to become as a perfect gift and as home decorations which people will love the fresh scent of the flowers filling the air in their home. Customer can walk in our shop or browse through our website for choosing the product they interested in. For bouquet flower, we sell fresh, preserved and mixed flower which we guaranteed to provide the freshest bouquets and beautiful hand-arranged bouquet for the customer. Hence, indoor flowers consists of Fittonia, Gold Crest, Peperomia and Ajuga which is become high demand for indoor decorations nowadays. We also sell, fiber clay pot, glass pot, ceramic pot and plastic pot for our customer to have variety choose for their flower pot. The price are average and based on standard price in the market. The business venture was started on 5 February 2018. Total worker in our company is 6 people which is ourselves to fill these position likes general manager, financial manager, marketing manager and operation manager. We also hired 2 staff as delivery man. We believe that these position suit on our strength and ability to handle stress under it. We choose Selangor to open our shop which specifically located at Ground Floor, NO 3A-53-01, Jln Medan Pusat Bandar 8A, Seksyen 9, 43650 Bandar Baru Bangi, Selangor because of its strategic location and near with our target market. Hanna Petals,BabyLyd Florist N Gift, 101 Florist Sdn Bhd and KCH were all our competitors which is not far away from our premise. All of them have their own strength. For example, Hanna Petals always updated flower design, BabyLyd Florist N gift Shop provide customized gifts, 101 Florist Sdn Bhd. give fast delivery and KCH Florist give discount for loyal customer. But they also have weakness which most of their flower and product not variety and quite expensive. They also charge high delivery. In order to introduce our product to our customers, we intend to prepare a product strategy that includes features of the product, brand name, packaging, protection of the product, trade name, and labeling. By using social media platform, such as Instagram, Facebook, Twitter and viral ads through Whatsapp about a product of ours. We also use outdoor ads as our campaign, which is a banner as ours initiative. Lastly, we also using printing media such as business cards that can be given to people so they can get know better about our product.